2023
DOI: 10.1108/sajbs-11-2021-0406
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic modeling of marginal expected shortfall under economic sensitivity: empirical evidence from Pakistan

Abstract: PurposeSystemic risk is of concern for economic welfare as it can lower the credit supply to all the sectors within an economy. This study examines for the first time the complete hierarchy of variables that drive systemic risk during normal and crisis periods in Pakistan, a developing economy.Design/methodology/approachSecondary data of the bank, sector and country variables are used for the purpose of the analysis spanning from 2000 to 2020. Systemic risk is computed using marginal expected shortfall (MES). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 77 publications
(164 reference statements)
1
0
0
Order By: Relevance
“…Further, this organization seeks to build strong relationships with its customers. As these results are consistent with the study (Hanif et al, 2021). The results of the analytical descriptive statistics also revealed that the arithmetic averages related to sustainable promotion came with a high level of importance from the point of view of the research sample.…”
Section: Discussion Of Resultssupporting
confidence: 90%
“…Further, this organization seeks to build strong relationships with its customers. As these results are consistent with the study (Hanif et al, 2021). The results of the analytical descriptive statistics also revealed that the arithmetic averages related to sustainable promotion came with a high level of importance from the point of view of the research sample.…”
Section: Discussion Of Resultssupporting
confidence: 90%